2021
DOI: 10.3389/fgene.2021.682565
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Disease Ontology by Instances of Atypical PKHD1 and PKD1 Genetics

Abstract: BackgroundAutosomal polycystic kidney disease is distinguished into dominant (ADPKD) and recessive (ARPKD) inheritance usually caused by either monoallelic (PKD1/PKD2) or biallelic (PKHD1) germline variation. Clinical presentations are genotype-dependent ranging from fetal demise to mild chronic kidney disease (CKD) in adults. Additionally, exemptions from dominant and recessive inheritance have been reported in both disorders resulting in respective phenocopies. Here, we comparatively report three young adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Although it is reasonable to speculate that patients with mild disease and those without an established familial history (more than 50% of unsolved patients in our cohort are sporadic) escaped an early clinical observation, it is also possible that in some patients with a family history, we missed the causative mutation. About this, we cannot rule out the presence of mutations in additional genes besides PKD1 and PKD2 (i.e., GANAB , HNF1b , DNAJB11 , PRKCSH, ALG8 , PKHD1 ) which have rarely been found in association with atypical or milder forms of ADPKD or, in addition to variants in the main two genes, worsened the clinical picture, likely by reducing the polycystin dosage [18, 34, 39, 55, 56]. Notably, in 17 out of 26 unsolved patients, we sequenced the GANAB gene without finding any pathogenic variants (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is reasonable to speculate that patients with mild disease and those without an established familial history (more than 50% of unsolved patients in our cohort are sporadic) escaped an early clinical observation, it is also possible that in some patients with a family history, we missed the causative mutation. About this, we cannot rule out the presence of mutations in additional genes besides PKD1 and PKD2 (i.e., GANAB , HNF1b , DNAJB11 , PRKCSH, ALG8 , PKHD1 ) which have rarely been found in association with atypical or milder forms of ADPKD or, in addition to variants in the main two genes, worsened the clinical picture, likely by reducing the polycystin dosage [18, 34, 39, 55, 56]. Notably, in 17 out of 26 unsolved patients, we sequenced the GANAB gene without finding any pathogenic variants (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Keyword searches in PubMed using "PKD1" plus "homozygote", "incomplete penetrant", "hypomorphic", "biallelic" or "trans heterozygous" identified further studies reporting PKD1 "hypomorphic" variants [44][45][46][47][48][49]. Notably, the Durkie study reported a high prevalence of biallelic inherited "hypomorphic" PKD1 variants in very early onset PKD [48].…”
Section: Autosomal Dominant Diseasesmentioning
confidence: 99%